Girl last seen - Laurin, Nina (New York : Grand Central Publishing, 2017)
"Two missing girls. Thirteen years apart. Olivia Shaw has been missing since last Tuesday. She was last seen outside the entrance of her elementary school in Hunts Point wearing a white spring jacket, blue jeans, and pink boots. I force myself to look at the face in the photo, into her slightly smudged features, and I can't bring myself to move. Olivia Shaw could be my mirror image, rewound to thirteen years ago. If you have any knowledge of Olivia Shaw's whereabouts or any relevant information, please contact... I've spent a long time peering into the faces of girls on missing posters, wondering which one replaced me in that basement. But they were never quite the right age, the right look, the right circumstances. Until Olivia Shaw, missing for one week tomorrow. Whoever stole me was never found. But since I was taken, there hasn't been another girl. And now there is"--
Keywords: Adult child sexual abuse victims -- Fiction; KIdnapping victims -- Fiction; Deja vu -- Fiction; FICTION / Suspense; Psychological fiction; Suspense fiction